Urgensi Manajemen Peningkatan Mutu Pendidikan - Putri, Meliani; Effane, Anne (Karimah Tauhid, 2023)
Classroom management is a benchmark for achieving the intended learning objectives Effective and efficient in the educational process, as a rule, educational goals It is calculated that this is achieved if classroom management has been carried out properly at the school alone. Classroom management is defined as teacher fees from classroom teachers Guide students in class planning or planning so you can plan and you can At the same time it creates a atmosphere that fun and always encourage students to participate and participate actively active in learning in class so that such a favorable environment help the success of the previously planned curriculum. When writing articles that are the result of the author's thoughts, the writing method is used As a method of writing or literature, namely taking information from articles or books Lessons related to the topics discussed. Hence the urgency to achieve classroom management planned learning objectives From the point of view, criteria and different indicators We can assume that the quality of education can be improved when schools have done so 1) government support, 2) leadership effective school principals, 3) good quality teacher performance, 4) appropriate curriculum and quality graduates, 5) efficient organizational culture and climate, 6) community support and parents of students. The application of leadership in improving the quality of education is the solution real hope to be able to master education quality indicators together Synergy to improve the quality of education.